2012
DOI: 10.1111/j.1365-2648.2012.06048.x
|View full text |Cite
|
Sign up to set email alerts
|

A critique of the National League for Nursing/Jeffries simulation framework

Abstract: Empirically supported definitions of concepts would strengthen the framework and help educators to consistently produce and identify positive outcomes. Additional rigorous research is necessary to further test relationships among concepts and the associated concept variables in the framework. More studies outside of the United States are needed to confirm the framework is relevant to nursing programs in other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…The use of simulation as a pedagogical approach is widespread and rapidly expanding in nurse education [1,2] . Through the use of human patient simulation (HPS), realistic and holistic clinical situations can be recreated on campus [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of simulation as a pedagogical approach is widespread and rapidly expanding in nurse education [1,2] . Through the use of human patient simulation (HPS), realistic and holistic clinical situations can be recreated on campus [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Applying this model in a national multi-site, multi-method project, Jeffries and Rizzolo (2006) found that debriefing was the most important feature in simulation design, and variables such as collaboration, problem-solving and high expectations were the essential education practices in simulation teaching. Favourable student outcomes such as increased student satisfaction, confidence and improved skill performance were also reported by a critique article of the framework of simulation model (Lafond & Van Hulle Vincent 2013). Yet, many of its concepts and propositions in the framework require further study.…”
Section: Introductionmentioning
confidence: 87%
“…Simulation design includes five other important constituents: objectives, fidelity, problem-solving, student support and debriefing. Learning outcomes may be evaluated by five indicators: knowledge, skill performance, learner satisfaction, critical thinking and self-confidence (Jeffries & Rogers 2009, Lafond & Van Hulle Vincent 2013. Applying this model in a national multi-site, multi-method project, Jeffries and Rizzolo (2006) found that debriefing was the most important feature in simulation design, and variables such as collaboration, problem-solving and high expectations were the essential education practices in simulation teaching.…”
Section: Introductionmentioning
confidence: 97%
“…[23][24][25][26] It can also increase learners' confidence in their skills. [27,28] Finally, successful teamwork between professionals affects patients' experience of the quality of the overall care delivered. [29] 3.…”
Section: Introductionmentioning
confidence: 99%